Effect of gonadectomy and estradiol on the expression of insulin signaling cascade genes in female and male mice - T. V. Iakovleva; N. E. Kostina; E. N. Makarova; N. M. Bazhan (Вавиловский журнал генетики и селекции, 2020)
A positive effect of estradiol on insulin sensitivity has been shown for females and males. Insulin sensitivity is higher in females than in males, and males show a greater tendency to develop metabolic disorders. It is believed that these sex differences are due to a protective effect of estradiol in females, but not in males. Estradiol is a steroid hormone, and its effect is due to the modulation of target gene expression, but the effect of estradiol on the expression of genes encoding insulin signal transduction and glucose transport has not been sufficiently studied. The aim of the study was to compare the molecular mechanisms of the estradiol influence on insulin sensitivity in mice of both sexes. The effect of gonadectomy and estradiol (1 μg/animal, three days) on the expression of insulin signaling cascade genes in muscle, adipose tissue, and liver, as well as on the expression of Fgf21, estradiol receptors (Esr1/2), and transcription factor Stat3 in the liver in female and male mice was investigated. Estradiol levels were lower and glucose blood levels and insulin resistance were higher in Sham operated (Sham) males compared to Sham females. Irs2, Pik3cd, and Esr1/2 mRNA levels were lower in the liver of Sham males than in Sham females. In females, gonadectomy reduced the level of estradiol in the blood, increased insulin resistance and blood glucose levels compared to Sham females. Administration of estradiol to gonadectomized females decreased blood insulin levels and insulin resistance. In males, gonadectomy, on the contrary, increased the blood estradiol level, decreased blood insulin level and insulin resistance. Estradiol did not affect the parameters studied in males. The development of insulin resistance in gonadectomized females was associated with a decreased expression of the Irs2 gene in the liver. Increased insulin sensitivity in gonadectomized males was associated with increased levels of Irs2 and Pik3cd mRNA in the liver. It can be assumed that increasing the level of estradiol in the blood activates the expression of the Irs2 gene in the liver regardless of animal sex. Also, estradiol seems to regulate the transport of glucose in adipose tissue regardless of animal sex: in females and males, an increase in the blood estradiol level was associated with a decrease in the expression of the Slc2a4 gene in adipose tissue. Thus, the effects of estradiol on the expression of insulin cascade genes do not seem to depend on animal sex, but have tissue specificity. Since the molecular mechanism of estradiol influence on the expression of insulin cascade genes in females and males is the same, the cause of sexual differences in insulin sensitivity and the rate of development of metabolic disorders may be a decrease in the level of estradiol in the blood, as well as a decrease in the expression of estradiol receptors in the liver in males compared to females.